2015
DOI: 10.1177/1071100714568868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Absorbable and Nonabsorbable Sutures for Repair of Achilles Tendon Rupture With a Suture-Guiding Device

Abstract: Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…19 Kocaoglu et al evaluated absorbable and non-absorbable sutures for Achilles tendon repair with a suture-guiding device and they found similar functional results with both suture types but less suture reaction with absorbable sutures. 20 Similar to the literature, our results showed that this technique provides patients an early return to work, improved AOFAS and Thermann scores, with minimal risk of complications.…”
Section: Aktas and Kocaoglu Compared Clinical And Functional Results supporting
confidence: 88%
“…19 Kocaoglu et al evaluated absorbable and non-absorbable sutures for Achilles tendon repair with a suture-guiding device and they found similar functional results with both suture types but less suture reaction with absorbable sutures. 20 Similar to the literature, our results showed that this technique provides patients an early return to work, improved AOFAS and Thermann scores, with minimal risk of complications.…”
Section: Aktas and Kocaoglu Compared Clinical And Functional Results supporting
confidence: 88%
“…In a prospective cohort study, Kocaoglu et al evaluated patients who underwent repair with the use of either number-2 braided nonabsorbable sutures or braided polyglactin absorbable sutures 28 . Similar outcomes were observed, leading the authors to recommend the use of absorbable sutures.…”
Section: Achilles Tendon Rupturementioning
confidence: 99%
“…There are studies which have reported that there is a greater rate of sural nerve damage in the open surgical repair techniques [12]. Although there are many treatment options for the treatment of acute Achilles tendon rupture, there are new techniques continuously described by various authors and satisfactory results have been reported [13][14][15][16][17]. However, in the current approaches, no treatment algorithm has yet been widely shown to have any superiority over other techniques.…”
Section: Discussionmentioning
confidence: 99%